Theoretical analysis of the quartic autocatalytic reaction of a thermally radiative ternary hybrid nanofluid in a stratified porous medium - M .Ajayi, Tunde; W. Ogunsola , Amos; A. Ajala , Olusegun (International Journal of Advanced Mathematical Sciences, 2023)
Quartic autocatalytic form of chemical reaction has valuable interference in catalysis, manufacturing of ceramics, and production of polymers. Motivated by this, the present work examined the quartic autocalytic chemical reaction of an hybrid nanofluid in the presence of thermal stratification, radiation, porosity. Similarity transformation method was employed to convert the governing equations into ordinary differential equations. The existence and uniqueness of a solution was examined, and numerical solution thereafter obtained. Results obtained were shown in figures.